Evaluation of severity scoring systems in patients with severe community acquired pneumonia - Spasovska Katerina (Sciendo, 2021)
Background. The aim of this study was to evaluate the ability of severity scoring systems to predict 30-day mortality in patients with severe community-acquired pneumonia.